Evaluation of long-term selection for part period egg number in White Leghorn chicken-correlated responses* - REDDY, B L N; SINGH, RAJVIR; KATARIA, M C; SHARMA, DEEPAK (The Indian Journal of Animal Sciences, 2014)
Data on 20 659 pullets which were the progenies of 40 to 50 sires and 160 to 200 dams per generation of a strain (IWH) if White Leghorn under long term selection for part period egg production over 24 generations were studied. Realised genetic responses per generation in over all period were -0.92 day in ASM, 3.38G in 20 weeks bw, -4.92g in 40 weeks bw and -0.07g in 40 weeks egg weight. The decline in egg weight was comparatively much lower in later part as compared to early part of the study. Age at sexual maturity showed a significant decline over the period of selection and significant negative correlated response was observed in early periods. For 20 weeks body weight in the over all period realized observed in body weight at 40 weeks of age. There was poor agreememnt between expected and realized responses for all the correlated traits. Realized heritabilities were much lower in the last generation than the first generations.